The Influence of Macroeconomics and the EIDO Index on Stock Price Movements - Septyaningrum, Ariana Anjas; Hasmarini, Maulidyah Indira (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
In general, stock price movements in Indonesia have been described with the Composite Stock Price Index (IHSG). This study aims to determine the impact of the variables Exports, Exchange Rates, Money Supply, Interest Rates, and the EIDO Index (MSCI Indonesia) on stock price movements. This data used secondary data with a timeseries data. Observations were made on the closing price of the Composite Stock Price Index each month, and involved macroeconomic factors such as, Export rate, Exchange Rates, Interest Rates, Money Supply, as well as the EIDO Index variable for the period of January 2019 to June 2023. In this study, the data analysis model used is Multiple Linear Regression, and the data is processed using E-views 10. In the results of this study, it was found that the level of exports, money supply, exchange rate, EIDO index respectively have a significant effect on positive direction to stock price movements. Meanwhile, interest rates have no significant effect on stock price movements.